Necessary optimality conditions for higher-order infinite horizon variational problems on time scales - Martins, N.
We obtain Euler-Lagrange and transversality optimality conditions for higher-order infinite horizon variational problems on a time scale. The new necessary optimality conditions improve the classical results both in the continuous and discrete settings: Our results seem new and interesting even in the particular cases when the time scale is the set of real numbers or the set of integers. © 2012 Springer Science+Business Media, LLC.